+0  
 
0
37
3
avatar

the radical equation: \(\sqrt{{q^2\over 2}+11} = q - 1\)

i then have to square both sides; but how should i square q - 1?

and after i squared both sides, what should i do next?

 
Guest Oct 11, 2017
social bar

Best Answer 

 #1
avatar
+1

Solve for q:
sqrt(q^2/2 + 11) = q - 1

Raise both sides to the power of two:
q^2/2 + 11 = (q - 1)^2

Expand out terms of the right hand side:
q^2/2 + 11 = q^2 - 2 q + 1

Subtract q^2 - 2 q + 1 from both sides:
-q^2/2 + 2 q + 10 = 0

Multiply both sides by -2:
q^2 - 4 q - 20 = 0

Add 20 to both sides:
q^2 - 4 q = 20

Add 4 to both sides:
q^2 - 4 q + 4 = 24

Write the left hand side as a square:
(q - 2)^2 = 24

Take the square root of both sides:
q - 2 = 2 sqrt(6) or q - 2 = -2 sqrt(6)

Add 2 to both sides:
q = 2 + 2 sqrt(6) or q - 2 = -2 sqrt(6)

Add 2 to both sides:
q = 2 + 2 sqrt(6) or q = 2 - 2 sqrt(6)

sqrt(q^2/2 + 11) ⇒ sqrt(1/2 (2 - 2 sqrt(6))^2 + 11) = sqrt(25 - 4 sqrt(6)) ≈ 3.89898
q - 1 ⇒ (2 - 2 sqrt(6)) - 1 = 1 - 2 sqrt(6) ≈ -3.89898:
So this solution is incorrect

sqrt(q^2/2 + 11) ⇒ sqrt(1/2 (2 + 2 sqrt(6))^2 + 11) = sqrt(25 + 4 sqrt(6)) ≈ 5.89898
q - 1 ⇒ (2 + 2 sqrt(6)) - 1 = 1 + 2 sqrt(6) ≈ 5.89898:
So this solution is correct

The solution is: q = 2 + 2 sqrt(6)

 
Guest Oct 11, 2017
Sort: 

3+0 Answers

 #1
avatar
+1
Best Answer

Solve for q:
sqrt(q^2/2 + 11) = q - 1

Raise both sides to the power of two:
q^2/2 + 11 = (q - 1)^2

Expand out terms of the right hand side:
q^2/2 + 11 = q^2 - 2 q + 1

Subtract q^2 - 2 q + 1 from both sides:
-q^2/2 + 2 q + 10 = 0

Multiply both sides by -2:
q^2 - 4 q - 20 = 0

Add 20 to both sides:
q^2 - 4 q = 20

Add 4 to both sides:
q^2 - 4 q + 4 = 24

Write the left hand side as a square:
(q - 2)^2 = 24

Take the square root of both sides:
q - 2 = 2 sqrt(6) or q - 2 = -2 sqrt(6)

Add 2 to both sides:
q = 2 + 2 sqrt(6) or q - 2 = -2 sqrt(6)

Add 2 to both sides:
q = 2 + 2 sqrt(6) or q = 2 - 2 sqrt(6)

sqrt(q^2/2 + 11) ⇒ sqrt(1/2 (2 - 2 sqrt(6))^2 + 11) = sqrt(25 - 4 sqrt(6)) ≈ 3.89898
q - 1 ⇒ (2 - 2 sqrt(6)) - 1 = 1 - 2 sqrt(6) ≈ -3.89898:
So this solution is incorrect

sqrt(q^2/2 + 11) ⇒ sqrt(1/2 (2 + 2 sqrt(6))^2 + 11) = sqrt(25 + 4 sqrt(6)) ≈ 5.89898
q - 1 ⇒ (2 + 2 sqrt(6)) - 1 = 1 + 2 sqrt(6) ≈ 5.89898:
So this solution is correct

The solution is: q = 2 + 2 sqrt(6)

 
Guest Oct 11, 2017
 #2
avatar
0

once you got -q^2/2 + 2q - 10 = 0, why would you wanna multiply both sides by -2? is a denominator not allowed? 

 
Guest Oct 11, 2017
 #3
avatar+76837 
+1

 

Multiplying through by -2  sets it up for completing the square........

 

cool cool cool

 
CPhill  Oct 11, 2017

21 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details